DAMPAK ALOKASI ANGGARAN PENGELUARAN PEMBANGUNAN TERHADAP PEREKONOMIAN INDONESIA: SUATU ANALISIS SIMULASI KEBIJAKAN - M. SINAGA, BONAR; HENDRANATA, ANTON (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 1 Februari 2005)
This study aims (1) to construct Econometric Input-Output Model for Indonesia, which emphasizes the linkage between sectors, and (2) to analyze the impact of budget allocation policy of development expenditure on Indonesian economy. The model, which construct by combining the advantages of input-output model and econometric model, is called Model Input-Output Ekonometrika Indonesia. The model consists of 112 dynamic simultaneous equations, and it uses secondary data from 1980-2000. The equation’s parameters are estimated by using the combination of three estimation methods: (1) Ordinary Least Squares, (2) First Order of Autoregressive, and (3) Second Order of Autoregressive. The model is validated by Gauss-Siedel Method and it is used for policy simulation analysis of budget development expenditure. The study shows that the impact of budget reallocation of development expenditure on Indonesian economy (final demand, output, income, and sectoral employment) is better than the budget allocation of development expenditure in RAPBN (National Budgetary Plan) 2002. Plantation sector gave the highest contribution in supporting the output multiplier and high income. Furthermore, the food, beverages, and tobacco industries gave the highest contribution in creating high employment multiplier.
Keywords: Econometric Input-Output, Budget Allocation, Policy Impact Analysis, Multiplier